2002
DOI: 10.2114/jpa.21.277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Room Temperature on Physiological and Subjective Responses during Whole-body Bathing, Half-body Bathing and Showering.

Abstract: The effects of bathroom thermal conditions on physiological and subjective responses were evaluated before, during, and after whole-body bath (W-bath), halfbody bath (H-bath) and showering. The air temperature of the dressing room and bathroom was controlled at 10°C, 17.5°C, and 25°°C. Eight healthy males bathed for 10 min under nine conditions on separate days. The water temperature of the bathtub and shower was controlled at 40°C and 41°C, respectively. Rectal temperature (Tre), mean skin temperature (T sk),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 12 publications
2
20
0
1
Order By: Relevance
“…Typically, bathers leave the cool or cold environment (especially in winter) of the dressing room and immerse themselves deeply in hot water (40-43 8C) where they sit with the water up to their shoulders. Japanese researchers have long suspected that this style of bathing may have an influence on the cardiovascular system and hemodynamics [3][4][5][6][7][8]. Despite considerable research into this bathing style, it is still unclear what actually triggers a lapse in consciousness or sudden death in the elderly during bathing.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, bathers leave the cool or cold environment (especially in winter) of the dressing room and immerse themselves deeply in hot water (40-43 8C) where they sit with the water up to their shoulders. Japanese researchers have long suspected that this style of bathing may have an influence on the cardiovascular system and hemodynamics [3][4][5][6][7][8]. Despite considerable research into this bathing style, it is still unclear what actually triggers a lapse in consciousness or sudden death in the elderly during bathing.…”
Section: Introductionmentioning
confidence: 99%
“…These two differences might cause the large number of accidental deaths due to bathing in winter among the elderly in Japan. Although effects of bathing in hotter water in deep bathtubs on physiological and subjective responses have been reported on both the young Hashiguchi et at., 2002) and the elderly (Nagasawa et al, 2001;Chishaki et al, 2005: Asakawa et al, 2006, the effects of room temperature on these responses before, during and after bathing have been reported only for the young (Kanda et al, 1996;Hashiguchi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Hashiguchi et al, 2002;Yamazaki R., 2007) reported that the physiological strains during half-body bathing and bathing in cooler water are less than whole-body bathing and hotter water immersion. However, colder room temperatures made it more difficult to retain body warmth during and after half-body bathing and cooler water immersion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thus far the number of studies that have examined the thermophysiological response of the human body during bathing is limited, and most studies have used experimental approaches. Hashiguchi et al (2002), Tochihara (1999), and Ohnaka et al (1995) evaluated the effect of room temperature during and after bathing and the method of bathing (including immersion and shower bathing) on the thermophysiological response. Chiba et al (2005) clarified the cause of death and the risk factors that are related to sudden death in the Japanese senior population while bathing in a Japanese style "hot bath.…”
Section: Introductionmentioning
confidence: 99%